MASTERPLAN PENGELOLAAN SAMPAH MANDIRI DI KAWASAN BUKIT SEMARANG BARU - RR. Sasi Kirana Sari (Departemen Teknik Lingkungan Fakultas Teknik Universitas Diponegoro, 2013)
Bukit Semarang Baru (BSB) is a residential area with the concept of an independent city located in the western part of Semarang. As an independent region, BSB’s developer shall provide waste management facilities. To increase its purpose and economic value of waste, treatment is necessary, Material Recovery Facility can be an alternative. Thus, the design of waste management and the concept of MRF needed.To design a waste management master plan, evaluating existing systems, sampling to determine waste generation and composition with SNI 19-3964-1994 are needed, then subsequently designing the independent solid waste treatment with MRF system and calculates the required budget plan.Evaluation result shows that the management of solid waste in BSB is quite well but not in accordance with SNI 3242:2008 of Residential Waste Management and SNI 19-2454-2002 of Operational Techniques of Municipal Solid Waste Management. Sampling results show that people in Bukit Semarang Baru produce average waste by weight of 0.64 kg / person / day with a volume of 3.65 L / person / day, thus having density of 175.51 kg/m3. BSB waste composition comprising 53.95% of organic waste, paper (9.26%), HDPE (8.45%) Other (7.64%), PP (4.02%) and PET (2.30% ) glass by 2.94%, 1.54% metal, wood and 1.36%, PS (1.08%), LDPE (0.09%), and PVC (0.00%), and other junk (7.37%). Solid waste management that will be applied in BSB consist of separation from the source, individual indirect collecting system with transfer station in BSB Jatisari, while BSB Mijen implement curbside collection system. Treatment of solid waste include composting or organics, briquettes processing, plastic rope spinning, size reduction and baling of plastics, cans and paper. This system requires an investment of Rp 4.661.599,00 with profit to Rp 9.419.793,00 per year by 2025.